Lama Bergadget Meningkatkan Resiko Adiksi Internet pada Anak Disabilitas Intelektual - Shinta Kusumawati; Amelia Aziz Daeng Matadjo (Jurnal Kesehatan Islam : Islamic Health Journal, 2022)
Abstract. Indonesia is one of the fourth largest smartphone usercountries in the world after China, India and the United States. Users ofsmartphones or gadgets are not only normal children and adolescentsbut also children and adolescents with disabilities. They use the interneteither as a medium of learning, entertainment or to fill theirspare time.This study aims to determine the level of internet addiction in childrenwith intellectual disabilities who use gadgets. Methods: The design wasa descriptive qualitative research with a cross sectional design. Theresearch data was taken using the Internet Addiction Test (IAT)questionnaire which was distributed via google form to the ABKcommunity in Malang City. The collected data were analyzed usinggamma correlation analysis. Results: the data of this study showed 8respondents consisting of 7 boys and 1 girl, with a long gadget per day2 hours (37.%%), and > 2 hours (62.5%). The level of internet addictionwas normal (37.5%), light (37.5%) and moderate (25%). The correlationof the length of time with the gadget per day on the level of addictionwas found to be p-value (0.739). Conclusion: There is no significantrelationship between length of time with gadgets per day with the levelof addiction in children with intellectual disabilities.